Two-dimensional electron systems in ATiO3 perovskites (A=Ca, Ba, Sr): Control of orbital hybridization and energy order - Rödel, T. C.; Vivek, M.; Fortuna, F.; Le Fèvre, P.; Bertran, F.; Weht, Ruben Oscar; Goniakowski, J.; Gabay, M.; Santander Syro, A. F. (American Physical Society, 2017)
Fil: Rödel, T. C.. Université Paris Sud; Francia. Synchrotron SOLEIL; Francia